New and Highly Potent Antitumor Natural Products from Marine-Derived Fungi: Covering the Period from 2003 to 2012 - Pejin, Boris; K. Jovanovic, Katarina; Mojovic, Milos; G. Savic, Aleksandar (Current Topics in Medicinal Chemistry, 2013)
This review covers the 2003-2012 literature data published for antitumor natural products from marine-derived fungi. The focus is on new and highly potent cytotoxic compounds, together with details related to the relevant fungal species. It describes 22 promising bioactives, originating mainly from symbiotic fungi. The chemical structures of all highlighted organic molecules are briefly discussed.
Keywords: novel leads